Analisis kebutuhan bahan ajar berbasis hots untuk meningkatkan kemampuan pemecahan masalah matematika mahasiswa - Nurwulandari, Ika; Rafiq, Muhammad Aunur (JPI (Jurnal Pendidikan Indonesia): Jurnal Ilmiah Pendidikan, 2020)
The teaching materials used by students have not made students skilled insolving problems. This study aims to analyze the needs of HOTS-based learningteaching materials for students of STKIP Muhammadiyah Blora. This research wasconducted at STKIP Muhammadiyah Blora. The subjects in this study were 30 3rdsemester students. The method used in this study is qualitative descriptionive research method. Sampling using purposive sampling. The research data was collected by observation techniques, interviews, and the dissemination of questionnaires. Thefindings in the study show that students are still low in problem solving and studentsneed high-level learning materials. Therefore, lecturers and students need mathlearning materials with HOTS.